Intensities of KCs E(4)1Σ+→(a3Σ+, X1Σ+) band system up to dissociation threshold: an interplay between spin-orbit, hyperfine and rovibronic coupling effects. (December 2022) - Klincare, I.; Tamanis, M.; Ferber, R.; Pazyuk, E.A.; Stolyarov, A.V.; Havalyova, I.; Pashov, A.
Highlights: High-resolution spectroscopy Coupled electronic states Line intensities Interplay between spin-orbit, hyperfine and rovibronic coupling effects Abstract: The relative intensity distribution in the rotationally resolved laser-induced fluorescence spectra belonging to the E ( 4 ) 1 Σ + → ( a 3 Σ 1 +, X 1 Σ + ) band systems of the KCs molecule was analyzed. The experimental intensities in doublet P, R progressions assigned to spin-allowed E → X and spin-forbidden E → a transitions up to their common ground dissociation limit were described in the framework of a coupled-channels (CC) deperturbation model applied for the interacting X 1 Σ + and a 3 Σ + states. The CC intensity simulation was based solely on fixed electronic structure parameters as functions of the internuclear distance R, namely: accurate empirical potential energy curves for all three states, ab initio estimates for matrix elements A ( R ) of the hyperfine structure (HFS), and transition dipole moments d E X ( R ) and d E a ( R ) . A comparison between the measured intensities and their theoretical counterparts demonstrates a strong competition between different intramolecular interactions. A weak spin-orbit coupling of the upper E ( 4 ) 1 Σ + state with the remote 3 Π states is responsible for appearance of the E → a vibrational bands for the intermediate v a -values. In turn, the HFS coupling between X 1 Σ + and a 3 Σ + states leads to peculiarities in E → ( X, a ) intensities, which are pronounced for high v X / a -values in the vicinity of K(4 2 S )+Cs(6 2 S ) dissociation threshold. Both adiabatic ro-vibrational and non-adiabatic electronic-rotational interactions explain the abrupt deviation of some observed P / R intensity ratios from the expected Hönl-London factors.